2019
DOI: 10.3390/su11226356
|View full text |Cite
|
Sign up to set email alerts
|

Energy Benchmarking of Existing Office Stock in Spain: Trends and Drivers

Abstract: Buildings play a central role in the clean energy transition, which is why it is vital to understand how energy is consumed in this sector. Energy performance certificate databases are considered a key source of information on the characteristics of built building stock. Despite a growing portfolio of studies based on information from such databases, little is known about energy consumption in offices. This paper explores the modelled energy performance of existing offices in Spain, using data from 13,701 ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The building type to search was chosen based on Gangolles et al's [58] study that concluded that there is a growing body of research utilizing energy performance certificate databases; however, there remains a limited understanding of energy consumption in office spaces. The studies by Armitage et al [59] and Hjortling et al [60] are the only studies referenced that conducted thorough analyses of final energy consumption within the office sector in England and Wales and in Sweden, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The building type to search was chosen based on Gangolles et al's [58] study that concluded that there is a growing body of research utilizing energy performance certificate databases; however, there remains a limited understanding of energy consumption in office spaces. The studies by Armitage et al [59] and Hjortling et al [60] are the only studies referenced that conducted thorough analyses of final energy consumption within the office sector in England and Wales and in Sweden, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Refs. [ [31] , [32] , [33] ]. These studies are also of great interest for us, however, they focus only in one region of Spain and represent insights outdated now.…”
Section: Methodsmentioning
confidence: 99%
“…In Catalonia, Spain, researchers exploiting data from about 14,000 certificates found that offices have an average annual energy use of 207.4 kWh/m 2 . Their energy ranking is mostly labeled in classes-C and -D (64%), while high energy ratings at the top ranked energy class A and -B are limited tõ 8% of the database [19]. NR buildings in Spain, were found to have slightly better energy performance than residential buildings, with an average energy consumption of 317.8 kWh/m 2 [15].…”
Section: Of 29mentioning
confidence: 99%